A interseccionalidade na poesia de Conceição Evaristo: uma proposta para o ensino fundamental – anos finais - Melo, Silvana Pereira (2020)
Conceição Evaristo's poetry has an identity forged as a woman and black. His text is built from the problematization of the stigma of ethnic-racial and gender segregation, echoing the voices of women and building a black-Brazilian female identity that reveals a trajectory of black woman's invisibility. From this perspective, literature goes beyond the condition of the art of words and puts itself at the service of the desires of a large portion of the population that has little representation in society, and, especially, in academic circles. In view of literary literacy (COSSON, 2014) and the social and aesthetic functions of literature, thought from Candido (1999), as well as the work with poetry in the classroom (PINHEIRO, 2018) and the approach on gender category in the light of intersectionality (BUTLER, 2003), this work proposes that, through the texts of Conceição Evaristo, students from the ninth grade of a public school in the city of João Pessoa, maintained by the state, can also build a new story , which makes it possible to understand the categories of gender and ethnic-racial. The work is constituted, in methodological terms, as an action of research. The interventionist proposal will happen through the readings of the poems: “I-woman”, “For the girl” and “Voices-women” so that, after the literary interpretation, we prioritize the identity marginalization of the black woman, as an element of dialogue, with in order to deconstruct a stereotype produced by a white and elite society. There will be workshops for reading documentary screenings and listening to music that will serve as discussion and guide for the production of poems, which will have performance presentations. The workshops will be planned based on the proposal of the basic sequence of Cosson (2014). In terms of theoretical foundation, we will still have Duarte (2010), Pinheiro (2018) and others who are interested in this work as support.